Surface water quality near the Erdenet mining area (Mongolian Journal of Geography and Geoecology, 2022)
This study presented the geochemical characteristics of surface water in the Khangal river basin near the Erdenet mining area of Mongolia, aiming to study the spatiotemporal hydrochemical characteristics and evaluate the water quality. A total of 20 surface water samples were collected during the summer (June) and fall (September) seasons of 2021 and major ions and pollution indicators were analyzed. 83.3% of all samples were dominated by sulphate ions, of which 50% were sulphate-calcium and 33.3% were sulphate-calcium-magnesium type water. The results of major ions presented spatial and temporal differences. Electrical conductivity (EC) values of the Erdenet and Khangal river were increasing gradually with distance, especially after mixing with wastewater discharges (from the south side) at the Erdenet-3 site and tailing pond seepage water at the Khangal river-1, 2 sites, providing clear evidence of anthropogenic impacts. The water of the Erdenet and Khangal rivers had relatively high mineralization and hardness compared to other rivers in Mongolia, and the class and group were different or sulphate-class predominance. According to the research conducted in recent years, the amount of mineralization and hardness of the Khangal river water increased compared to 46 years ago or before the start of the industry’s operation, the mineralization increased by 2.05 times in 2021, and the chemical composition was changed. Nitrite nitrogen, which is a domestic pollutant, was found relatively high (0.28-0.3 mg/l) in the samples taken from the Erdenet River-3 site, and this was  4.2 times higher than the MNS 4586:1998 standard, and classified as “highly polluted” compared to the Surface Classification Norm. Altanbulag’s water had high mineralization, hardness, and sulphate ion predominance, which may be related to natural origin, but the sudden increase in these parameters indicated a significant influence from tailing pond seepage water. Based on the results, recommendations on how to prevent river water pollution were made and measures to be taken were included. The findings of the study could be useful for water quality management of the basin.Уулын баяжуулах Эрдэнэт үйлдвэрийн районы гадаргын усны чанарХУРААНГУЙЭнэхүү судалгаа нь Эрдэнэт үйлдвэр орчмын Хангал голын сав газрын гадаргын усны геохимийн шинж чанар, түүний орон зай болон цаг хугацааны өөрчлөлтийг судлах, усны чанарыг үнэлэх зорилготой. Нийт 20 гадаргын усны сорьцыг 2021 оны зун (6-р сар) болон намар (9-р сар) 2 удаагийн давтамжтай цуглуулсан ба гол ионууд болон бохирдлын үзүүлэлтүүдийг шинжилсэн. Нийт дээжийн 83.3%-д сульфатын ион зонхилж, үүнээс 50% нь сульфат-кальци, 33.3% нь сульфат-кальци-магнийн найрлагатай байв. Гидрохимийн судалгааны үр дүн нь цаг хугацаа болон орон зайн өөрчлөлтийг харуулж байсан ба  Эрдэнэт болон Хангал голын усны цахилгаан дамжуулах чадвар нь урсгалын дагуудаа аажмаар нэмэгдэж байв. Ялангуяа Эрдэнэт-3 цэгт урд уулнаас саарал өнгөтэй хаягдал ус, Хангал-1,2 цэгт хаягдлын далангийн шүүрлийн ус тус тус нийлсний дараа цахилгаан дамжуулах чадвар нэмэгдэж байгаа нь антропоген хүчин зүйлийн нөлөөг илтгэж байна. Эрдэнэт болон Хангал голуудын ус нь Монгол орны бусад голуудаас харьцангуй өндөр эрдэсжилт, хатуулагтай байгаагийн гадна анги, бүлэг төрлийн хувьд өөр буюу сульфатын ангийн байна. Сүүлийн жилүүдэд хийсэн судалгаагаар Хангал голын усны эрдэсжилт, хатуулгийн хэмжээ нэмэгдэж байгаа бөгөөд 46 жилийн өмнөх буюу үйлдвэрийн үйл ажиллагаа эхлэхээс өмнөх үетэй харьцуулахад эрдэсжилт 2021 онд 2.05 дахин нэмэгдэж, химийн бүрэлдэхүүнд өөрчлөлт орсон байв. Эрдэнэт гол-3 цэгээс авсан сорьцод ахуйн бохирдолт болох нитритийн азот харьцангуй өндөр илэрч (0.28-0.3 мг/л), MNS 4586:1998” стандартаас 4.2 дахин их, ГУЦЗАН-той харьцуулахад “Их бохирдолттой” гэсэн ангилалд орж байна. Алтанбулагийн ус нь өндөр эрдэсжилт, хатуулагтай, сульфатын ион давамгайлсан байгаа нь байгалийн гаралтай байх талтай ч эдгээр үзүүлэлтүүд огцом нэмэгдсэн нь хаягдлын сангийн усны нөлөөлөл их байгааг илтгэж байна.Судалгааны үр дүн дээрээ үндэслэн хэрхэн голын усыг бохирдуулахгүй байх талын зөвлөмж өгч, авч хэрэгжүүлэх арга хэмжээг тусгасан.Түлхүүр үгс: Гидрохими, Хангал гол, Эрдэсжилт, Хатуулаг.